Impact, incidence and prevalence of musculoskeletal injuries in senior amateur male rugby: epidemiological study - Tondelli, E.; Boerio, C.; Andreu, M.; Antinori, S. (The Physician and Sportsmedicine, 2021)
Objectives Exposure to different types of injuries in rugby union is common. It is important to know about the injury epidemiology for medical teams care in order to optimize players´ performance and the treatment of common injuries, but there is limited specific information related to amateur rugby union. The purpose of this study is to determine the incidence, prevalence, injury burden, severity, nature of injuries sustained by senior amateur male rugby players from three clubs in Argentina during a given season.